NILAI KARAKTER DALAM CERITA RAKYAT YONOKHONG (KWADEWARE) DISTRIK WAIBU KABUPATEN JAYAPURA - Siswanto dan Asmabuasappe NFN (Balai Bahasa Provinsi Papua, 2019)
This research entitle Character Values in Cerita Rakyat Yonokhong (Kwadeware) Distrik Waibu Kabupaten Jayapura. The purpose of this research was to describe and explain the characters values contained in the Cerita Rakyat Yonokhong (Kwadeware) Distrik Waibu Kabupaten Jayapura. The character values described and explained include: carefully, never give up, be responsible, wise, brave to admit mistakes, assertive, polite, sincere, love of country, working together, brave, affectionate, obedient, alert, smart, honest, united, independent, strong, believe in supernatural powers, meticulous, and rely on supernatural powers. This research used a qualitative descriptive approach. The data in this research are the values of characters that comes from Cerita Rakyat Yonokhong (Kwadeware).